Absolute Normalization of the Three-Nucleon Transfer Reactions Cross Section in the Distorted-Wave Born Approximation Formalism. - Nubi, Olatunbosun Owolabi (Obafemi Awolowo University, 2014)
The three-nucleon transfer reaction cross section form factor for direct pick-up reactions (p,α) and (n,α), using DWBA formalism and shell model basis states, is obtained following an approach analogous to that by Towner and Hardy. Explicit calculations, with gaussian form for the interaction, are performed on the portion of the form factor which depends on the a-particle wave function and on the interaction potential